2021
DOI: 10.17305/bjbms.2020.5261
|View full text |Cite
|
Sign up to set email alerts
|

Extreme lateral interbody fusion (XLIF) in a consecutive series of 72 patients

Abstract: Extreme lateral interbody fusion (XLIF) has become the standard of minimally invasive lumbar segmental scoliosis treatment. Our objective is to determine the safety and efficacy of XLIF in spinal canal stenosis (SCS) and spondylodiscitis (SD). Patients treated with XLIF in our department between 2012 and 2018 were retrospectively analyzed. Patient records with clinical and radiographical parameters were evaluated. The patient cohort consists of 40 male and 32 female patients with a median age of 66.6 years. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
2
2
0
1
Order By: Relevance
“…Consistent with our research, Pojskic et al .’s experiment showed that the VAS improved after XLIF, which dropped from 8.8 to 2.8. 26 In Chen's research, the JOA score increased from 12 to 18.9, showing the same trend as our report. 27 It can be seen that XLIF is an effective operation for the treatment of lumbar degenerative diseases.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with our research, Pojskic et al .’s experiment showed that the VAS improved after XLIF, which dropped from 8.8 to 2.8. 26 In Chen's research, the JOA score increased from 12 to 18.9, showing the same trend as our report. 27 It can be seen that XLIF is an effective operation for the treatment of lumbar degenerative diseases.…”
Section: Introductionsupporting
confidence: 87%
“…The VAS of leg pain and JOA score improved significantly after operation in all groups and no difference was identified among the three groups at all time points, which showed the good effect of XLIF operation on nerve decompression. Consistent with our research, Pojskic et al .’s experiment showed that the VAS improved after XLIF, which dropped from 8.8 to 2.8 26 . In Chen's research, the JOA score increased from 12 to 18.9, showing the same trend as our report 27 .…”
Section: Introductionsupporting
confidence: 79%
“…Particularly for the surgical treatment of lumbar vertebra infection, the extreme lateral approach can directly reach and thoroughly expose the lesion space and vertebral body. Simultaneously, the spinal canal, spinal cord, and dura can be avoided, making the surgery safer ( 15 ). During this surgery, we directly exposed the intervertebral space of the lesion with a highly lateral approach, without harming the facet joints and compromising the spine's stability.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly noted deficit was ipsilateral thigh weakness, most frequent in spondylodiscitis patients, which the authors attributed to paravertebral muscle infection, rather than due to the DLIF approach itself. The authors also noted a higher rate of non-fusion when utilizing the DLIF approach, also attributed to infection, as well as shorter follow-up [ 16 ]. These collective findings underscore the need for formal guidelines for employing the DLIF approach in refractory osteomyelitis/discitis cases.…”
Section: Discussionmentioning
confidence: 99%